(3QhVI GdCYjGf aj CNHGQ eTGgjQ GdReGfs - (3GHf Ocjf , eMeO Hf CHj HcQ Hf Ydj Hf YHO Gdedc Hf MeGOj,J (B750 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdChd GdGNQ GdHGWf GdXGgQ s
(3HgG JbOje hJCNjQs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B55s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B929 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B76 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs